Formulation and in-vitro release studies of Ranibizumab (Lucentis) loaded liposomes - Ang, Jin Yan (2013)
Poor drug delivery to the posterior segment in patients’ eyes is a major obstacle to the treatment of ocular diseases due to its physiological and chemical barriers for transport of large molecular weight molecules such as proteins. In the past few decades, considerable research has been directed towards using lipid based vesicles such as liposomes as drug delivery carriers and results have been promising. In this report, liposomes will be studied as a drug delivery carrier for loading and release of a protein molecule, Ranibizumab (Lucentis) which is approved for the treatment of age related macular degeneration in clinics. Physical Characterization of Lucentis was carried out with the effect of incubation of Lucentis under temperature and Triton X-100. Charged liposomes were successfully fabricated with different known concentrations made from lipids using 1,2-Dimyristoyl-sn-glycero-3-phosphocholine (DMPC), 1,2-dimyristoyl-sn- 3-phosphatidylglycerol (DMPG), N-[1-(2,3-dioleoyloxy)-propyl]-N,N,N- trimethylammonium methyl sulfate (DOTAP). Liposomes sizing was performed by sequential extrusion through polycarbonate filters to achieve liposomes of defined size and homogenous distribution of vesicles. Lucentis was then loaded into preformed liposomes via passive and weak alkaline loading for drug releases studies. From drug release studies evaluation, liposomes with higher surface charges with matching acyl chain length of their lipids lead to a more controlled Lucentis release, except for positively charged liposomes. Neutral liposomes had the fastest release of Lucentis within four days, followed by positively charged liposomes in six days. Even though negatively charged liposomes had the slowest release, all the formulations had a burst of 70-80% drug release in Day 1, which suggest that Lucentis release could not be controlled due to various reasons as discussed in this report. In conclusion, negatively charged liposomes provide sustained release of Lucentis to a certain extent but further studies are warranted to improve its sustainability.